Molecular crowding‐based imprinted monolithic column for capillary electrochromatography. Issue 5 (4th February 2015) - Zong, Hai‐Yan; Liu, Xiao; Liu, Zhao‐Sheng; Huang, Yan‐Ping; Gaš, Bohuslav
<x xml:space="preserve">Abstract</x> Molecular crowding is a new approach to stabilizing binding sites and improving molecular recognition. In this work, the concept was applied to the preparation of imprinted monolithic columns for CEC. The imprinted monolithic column was synthesized using a mixture of d‐zopiclone (d‐ZOP)(template), methacrylic acid, ethylene glycol dimethacrylate, and poly(methyl methacrylate) (PMMA) (molecular crowding agent). The resulting PMMA‐based imprinted capillary was able to separate ZOP enantiomers in CEC mode. The resolution of enantiomer separation achieved on the d‐ZOP‐imprinted monolithic column was up to 2.09. Some polymerization factors, such as template‐monomer molar ratio, functional monomer‐cross‐linker molar ratio and the composition of the porogen, on the imprinting effect of resulting molecularly imprinted polymer (MIP) monolithic column were systematically investigated. Chromatographic parameters, including pH values, the content of acetonitrile and the salt concentration on chiral separation were also studied. The results indicated the addition of PMMA resulted in MIPs with superior retention properties and excellent selectivity for d‐ZOP, as compared to the MIPs prepared without addition of the crowding‐inducing agent. The results revealed that molecular crowding is an effective method for the preparation of a highly efficient MIP stationary phase for chiral separation in CEC.